Optimalisasi Tenaga Kerja Menggunakan Time and Motion Study untuk Meningkatkan Efisiensi Operasional Departemen Finishing Uncoated - Nur Wahid, Taufik; Ikhwanul Alifin, Fakhri (Industrial Engineering, Engineering of Faculty, Universitas Kadiri, 2024)
Optimizing the number of workers is an important factor in improving the company's operational efficiency by ensuring that each worker has an appropriate role and workload. This research aims to optimize the number of workers in a manufacturing company that produces processed paper in Karawang Regency. This study uses the time and motion study method to measure labor needs precisely. Initially, the number of workers in the uncoated finishing department was 14 people. Through the measurement of time and motion study, the ideal number of workers needed was obtained as many as 11 people. There was a difference of as many as 3 workers between the initial number and the measurement results. This result allows the company to optimize the number of workers according to operational needs. The benefits of this optimization include increased operational efficiency and labor cost savings, which can ultimately improve the company's profitability, competitiveness, and performance.